(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article is about the moral feelings of the person and the factors of their development in students, the sense of humanity and its social importance. It was discussed about turning humanitarianism, which is considered a moral feeling in students, into life habits.